Optimalisasi Peran Badan Usaha Milik Desa: (Studi Desa Puna Kecamatan Polen Kabupaten Timor Tengah Selatan) - Heni Enggelina Mona; Alfred O. Ena Mau; Yaherleof Foeh; Marthina Raga Lay (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
BUMDes is a village economic institution established to manage local potential, improve community welfare, and encourage village economic independence. However, in its implementation, BUMDes management often faces various obstacles, both in terms of human resources, institutional governance, and business management. This research employed a qualitative research method with a case study approach. Data collection techniques included observation, interviews, and documentation with informants including the village head, BUMDes administrators, and the Puna Village community. The research results show that the role of the Salebak Village-Owned Enterprise (BUMDes) in improving the village economy has not been optimal. This is due to limited human resource capacity, suboptimal institutional governance, and business management that has not developed sustainably. Nevertheless, BUMDes still has great potential to be developed through institutional strengthening, increasing human resource capacity, and developing partnerships with various parties. Therefore, a targeted development strategy is needed so that BUMDes can function optimally as a driver of the village economy and be able to provide real benefits for community welfare.